Tissue-engineered tubular substitutions for urinary diversion in a preclinical rabbit model - Wang, Qianliang; Liu, Qingling (Frontiers in Medicine, 2025)
ObjectiveTo develop and evaluate tissue-engineered tubular constructs using homologous adipose-derived stem cells (ASCs), smooth muscle cells (SMCs), and decellularized fish swim bladder (DFSB) matrix for urinary diversion in a rabbit model.MethodsRabbit ASCs and SMCs were isolated and expanded in vitro; cultured cells were seeded onto bilateral surfaces of DFSB scaffolds followed by 7-day incubation; cell-seeded matrices were shaped into tubular constructs; constructs underwent 2-week in vivo pre-vascularization within omental pouches. Experimental group rabbits (n=24) underwent complete bladder resection with replacement by pre-vascularized constructs, while control group (n=6) received identical implantation of acellular DFSB tubes. Histological evaluations were conducted at postoperative weeks 2, 4, 8, and 16; intravenous urography (IVU) was performed at 16-week endpoint.ResultsAll experimental animals survived until scheduled sacrifice with histological evidence of: (1) luminal multilayer urothelium, (2) organized smooth muscle tissue on abluminal surfaces, and (3) construct-wide neovascularization of varying diameters; IVU confirmed absence of urinary leakage, stricture, or obstruction. Conversely, all control animals died within 2 weeks post-operation; autopsy revealed urine leakage, extensive scar formation, and severe inflammation as mortality causes.ConclusionTissue-engineered tubular constructs fabricated from homologous ASCs, SMCs, and DFSB scaffold demonstrate feasibility as a viable urinary diversion alternative in rabbit models, showing functional tissue regeneration and superior outcomes versus acellular controls.